The Role of Inhibitory G Proteins and Regulators of G Protein Signaling in the in vivo Control of Heart Rate and Predisposition to Cardiac Arrhythmias - Ang, Richard; Opel, Aaisha; Tinker, Andrew (Frontiers in Physiology, 2012)
Inhibitory heterotrimeric G-proteins and the control of heart rate. The activation of cell signalling pathways involving inhibitory heterotrimeric G-proteins acts to slow the heart rate via modulation of ion channels. A large number of RGSs can act as GAPs to inhibitory G-proteins and thus it is important to understand the network of RGS-protein interaction. We will review our recent findings on in-vivo heart rate control in mice with global genetic deletion of various inhibitory G-protein alpha subunits. We will discuss potential central and peripheral contributions to the phenotype and the controversies in the literature.